Surface Porosity of Different Investment Materials with Different Mixing Techniques - Ahmed A Al-Ali; Luma M Al-Nema; Ibtehal H Al-Zubaidy (University of Mosul, College of Dentistry, 2009)
Aims: To evaluate and compare the number and surface area of surface porosities of different dental investment materials by using two mixing techniques. Materials and Methods: Two mixing techniques; manual and mechanical were used to prepare specimens for four dental investment materials: Biosint Supra, Rema Exakt, Rematitan Plus, and Deguvest soft. Computer programs are used to measure the number and surface area of the porosities to compare among them. ANOVA, Duncan multiple range test in addition to T-test were carried out to determine the significant difference at Parea of the porosities, there are high significant differences among the investment materials tested, and high significant difference is presented between the two mixing techniques tested with the manual mixing technique and showing higher value than the mechanical vacuum mixing technique. In relation to the number of porosities, there are no significant difference among the investment materials tested, but there are very high significant differences between the two mixing techniques tested with the manual mixing technique and showing higher value than the mechanical vacuum mixing technique. Conclusions: the number and surface area of the surface porosities differ from the different materials used, and differ in the same material by changing the mixing technique